1993
DOI: 10.1017/s0272263100011979
|View full text |Cite
|
Sign up to set email alerts
|

Explicit Instruction and Input Processing

Abstract: In this paper w e describe a n experiment in explicit instruction that compares traditional form-focused instruction a n d what w e call processing instruction. Traditional instruction involves explanation a n d output practice of a grammatical point. Processing instruction involves explanation a n d practice/experience processing input data, taking learner strategies in input processing a s t h e starting point for determining what explicit instruction should look like. Pretest a n d posttest measures involvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
448
8
10

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 449 publications
(499 citation statements)
references
References 22 publications
33
448
8
10
Order By: Relevance
“…The CIG outperformed the two output-based groups (IOG & COG) confirming the claims made by Ellis (1997) and VanPatten and Cadierno (1993) who proposed "that it is the manipulation of input (how learners perceive and process input) rather than output (how learners produce language output) that is more likely to result in the integration of intake into learners" implicit/declarative knowledge".…”
Section: Discussionsupporting
confidence: 79%
“…The CIG outperformed the two output-based groups (IOG & COG) confirming the claims made by Ellis (1997) and VanPatten and Cadierno (1993) who proposed "that it is the manipulation of input (how learners perceive and process input) rather than output (how learners produce language output) that is more likely to result in the integration of intake into learners" implicit/declarative knowledge".…”
Section: Discussionsupporting
confidence: 79%
“…It has addressed the question of whether the effects of processing instruction endure, diminish or disappear over time. Overall the results of these studies showed that there are short-term durative effects for sentence-level tasks (VanPatten and Cadierno 1993;Cadierno 1995;Benati, 2001Benati, , 2004Farley, 2001Farley, , 2004Cheng 2002;Morgan-Short 2006;Lee and Benati 2007). Learners in processing instruction groups tend to maintain their improved performance (from the pre-test to the immediate post-test) from immediate post-tests to delayed post-tests up to one month from the original instructional exposure.…”
Section: Previous Research On Durative Effectsmentioning
confidence: 86%
“…We already saw in our introduction in section 1 that both meaning and form play important roles in SLA. Pushing this discussion one step further, work in the Input Processing paradigm ( VanPatten and Cadierno, 1993), based on Krashen's (1977) input hypothesis, provides several relevant studies showing that "learners process input for meaning before they process it for form" (VanPatten, 1990;Wong, 2001). However, Norris and Ortega (2000) argued that simultaneously directing the learner's attention to form and meaning in the input does not hinder L2 development or reading comprehension.…”
Section: Relevant Sla Conceptsmentioning
confidence: 99%